Psychological evaluation in court in Lithuania: Present situation, problems and possible solutions - Valickas, Gintautas; Justickis, Viktoras; Čėsnienė, Ilona (Psichologija, 2006)
According to Law of Forensic Expertise of Lithuania, only a person who has sufficient legal and psychological knowledge and passed appropriate exams can obtain the status of an expert in forensic psychology. Unfortunately, the possibilities of professional psychologists (excluding clinical psychologists) to exercise forensic psychological expertise are limited without a good reason. Obscure rules of evaluation of qualifications and practical experience regulate the process of becoming a licensed expert in forensic psychology. These rules are not based on legal, professional or practical analysis. This is a result of the historical situation when for a long time psychological expertise has been considered to be part of psychiatry and was only additional „servicing“ activity of expertise of psychiatry. Problems of education and training of experts in forensic psychology (EEP) are described in this article. At present, demand for EFP services is growing. Judges, interrogation officers, investigators need more and more special knowledge in the field of psychology, especially when analyzing the ability of juvenile witnesses to provide credible information, the ability of juveniles to understand the situation and to provide their opinion in the cases of custody or adoption. At present, the number of EEPs remains the same. A lot of psychologists who have good knowledge and experience can only consult but cannot act as experts. There are no EFP to participate actively in research activities. Moreover, the Office of Forensic Psychiatry does not provide any information and refuses to coach psychology students on practical aspects of expert work. They withhold information on expertise methods as well. The Council of Experts does not include any psychologists, and psychiatry experts represent the opinion of psychologists too. One of the possible solutions to this situation is preparation of a new legal act on forensic psychology, which would regulate the status of psychological expertise according to the new modern approach. Detailed proposals are provided at the end of the article. Implementation of the proposals would encourage the competitive process of psychological expertise and facilitate involvement of the Lithuanian Psychological Association, scientific institutions and scientists working in this area.
Keywords: expert in forensic psychology; the Law of Forensic Expertise; legal act on forensic psychological expertise; adversarial forensic psychological expertise